Extraction of Asian ancient leaf, Piper betle using a modern and green technology - Ab. Hadi, Hazrina (2019)
Piper betle Linn. is an evergreen and perennial plant species with glossy heart-shaped leaves that is originated from Piperaceae family. Due to its characteristic odour and pungent taste, it is often recognized as an aromatic plant with various medicinal benefits, gained especially from the leaves. The variety of benefits of Piper betle is associated with the presence of many phytochemicals. One of the main chemical compounds abundantly found in Piper betle leaf is hydroxychavicol, which is classified in propenylphenol chemical group. The extraction of Piper betle leaves could be prepared by Soxhlet method which used deionized water and other organic solvents such as ethanol or dichloromethane. However, the conventional solvent extraction technique posed many disadvantages since it required lengthy extraction time, had poor extraction efficiency, and had harmful solvent remnants in the extract. Nevertheless, there is a recent extraction technique that has become an alternative to this conventional extraction method. It is known as subcritical water extraction and is often termed as hot water extraction, pressurized hot water extraction, pressurized low polarity water extraction, and superheated water extraction. This environment-friendly extraction technique uses water as the extraction solvent by applying subcritical conditions of a high temperature between 100 and 374℃ and a high pressure to maintain the liquid state of water. In this extraction method, the properties of water can be altered by regulating two main parameters i.e. temperature and pressure. Therefore, subcritical water has a great potential in extracting polar, semi-polar as well as non-polar bioactive compounds through the elevation of temperature. In this study, subcritical water extraction was adopted as a new approach to obtain Piper betle aqueous extract, which contained hydroxychavicol as the main active compound of interest. In order to determine the optimal extraction condition, extraction temperatures ranging from 40 to 180℃ and extraction time intervals of 10 to 90 min were tested. To sum up, after optimizing both extraction parameters of temperature and time interval, the highest amount of hydroxychavicol that was extracted from Piper betle leaves using subcritical water extraction was 7.53 ± 0.03%, w/w, obtained at an extraction temperature of 100℃ with 60 min time interval in the total run time of 180 min at a pressure of 1500 psi. As a result, the extraction temperature of 100℃ and the extraction time interval of 60 min are selected as the optimal condition for subcritical water extraction of Piper betle aqueous extract containing hydroxychavicol from Piper betle leaves for producing a total hydroxychavicol yield of 30.58 ± 0.12 mg/g Piper betle leaves. From this study, it is proven that both extraction parameters of high temperature and time play significant roles to ensure an effective extraction process of the desired compound.